Sectoral Volatility in Borsa Istanbul: A GARCH-based Comparative Analysis - Bulut, Emre (My University, 2024)
This study delved into the complex landscape of sectoral volatility dynamics within Borsa Istanbul, a dynamic emerging market, using the Generalized Autoregressive Conditional Heteroskedasticity (GARCH) model. By analyzing a dataset spanning from March 1, 2013, to August 16, 2023, the research examined how different sectors respond to market shocks and how these responses vary across sectors. The findings revealed distinct volatility behaviors among sectors, with the BIST Financial Leasing Index (FINK) displaying heightened vulnerability to external shocks, while the BIST Banking Index (BNK) and BIST Financial Index (MALI) exhibited comparatively milder volatility responses. Policymakers, regulators, and investors can utilize these insights to tailor risk management strategies, enhance market stability, and construct portfolios that align with risk preferences. This research enriches the understanding of sectoral dynamics in emerging markets, offering a foundation for future investigations into the intricate interplay between sectors, shocks, and volatility patterns.
Keywords: BIST; risk; GARCH; Volatility